PENGARUH KEBIJAKAN DIVIDEN TERHADAP KEKAYAAN PEMEGANG SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Bayu Malindo Putra; Henny Setyo Lestari (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2016)
This study discusses the effect of the dividend per share, retained earnings per share, return on equity, and lagged price per share to the market price per share on manufacturing companies listed in Indonesia Stock Exchange (IDX). The sampling technique used in this research is purposive sampling. Samples are 33 companies listed in the Indonesia Stock Exchange (IDX) for five years from 2010 to 2014. The dependent variable in this study is the market price per share, while the independent variable is the dividend per share, retained earnings per share, return on equity, and lagged price per share. The method used in this research is multiple regression. The results show that there are positive influence between the dividend per share, retained earnings per share, return on equity and lagged price per share to the market price per share.